GA3 priming, biopriming and hydropriming effect on quality nursery production of China aster (Callistephus chinensis) - Shabnam Pangtu; Puja Sharma; SR Dhiman; Prashant Sharma; Divesh Thakur (Current Horticulture, 2024)
The study was carried out at Dr YS Parmar University of Horticulture and Forestry, Nauni, Solan, on China aster [Callistephus chinensis (L.) Nees] cv ‘Poornima’ and ‘Kamini’ in nursery under open field conditions in randomized block design (factorial) comprising eight seed priming treatments, viz. control, hydropriming with water, priming with GA3 (50, 100 and 150 ppm) and biopriming with Trichoderma viride @ 1× 104 cfu/ml, 1× 105 cfu/ml and 1× 106 cfu/ml for 24 hr. There was maximum speed of germination (18.97, 21.58), germination percentage (83.17, 86.33 %), root length (2.87, 2.93 cm), shoot length (6.39, 6.59 cm), seedling length (9.26, 9.52 cm), seedling dry weight (227.67, 248.30 mg), seed vigour index-I (769.89, 822.19), seed vigour index-II (18,934.33, 21,436.62); minimum time taken to seed germination (12.72, 11.33 days) and days required to reach 4-6 leaf stage (23.70, 22.33 days) with priming treatment GA3 (100 ppm) in Poornima and Kamini, respectively. Hence, it is concluded that seeds of Kamini treated with GA3 (100 ppm) for 24 hr obtained best results for most of the desirable character for quality nursery production of China aster.